Pengelolaan Arsip Sesuai Standar Internasional (ISO 15489-1:2016) Studi Kasus Pengelolaan Arsip Bank Indonesia - Riko Priyatmo Ramudin (Diplomatika: Jurnal Kearsipan Terapan, 2019)
This article discusses Management of Records that adapts International Standards in the field of archives, namely ISO 15489-1: 2016 on Documentation: Concepts And Principles - Records Management.  Management of Records that compliance with international standards is very important for an organization to create authentic, reliable, complete and usable so that it can support organizational performance. This article is important because until now there is only one institution in Indonesia that applies international standards in the field of records,  Bank Indonesia. The aim is to find out how to manage records in Bank Indonesia that compliance international standards (ISO: 15489-1: 2016). The research method used is a qualitative method with primary and secondary data sources. Bank Indonesia Document Management Policy (MDBI) as a basis for Records Management according to international standards. MDBI refers to the management of records which consists of policies and responsibilities, systems and processes.